Comparison of CMOS and PSP intraoral digital sensors in the diagnosis of secondary caries adjacent to amalgam restorations - S Mehralizadeh; S Nemati Anaraki; M Orshesh (Islamic Azad University, 2017)
Background and Aim: Considering the consequences of false positive (FP) and false negative (FN) diagnoses as well as the lack of information on the diagnostic ability of photostimulable phosphor plate (PSP) and complementary metal oxide semiconductor (CMOS) sensors in the detection of secondary caries, this study aimed to compare the diagnostic ability of these two sensors in the detection of secondary caries adjacent to amalgam restorations. Materials and Methods: This diagnostic study was performed on 40 intact permanent premolars. Class II cavities were prepared and restored with amalgam. Periapical radiography was performed by using PSP and CMOS sensors via parallel technique. A 0.5-mm round bur was used to create another cavity under amalgam restorations. To simulate secondary gingival caries at the cementoenamel junction (CEJ), the samples were placed inside 0.1M lactic acid solution and were incubated at 37°C for three weeks. The teeth were placed in gypsum blocks and were radiographed again by CMOS and PSP sensors. The presence of decay was determined by an oral and maxillofacial radiologist, and the results were recorded in datasheets and were statistically analyzed by the ratio test. Results: The sensitivity and specificity of PSP in caries detection were 52.5% and 77.5%, respectively. The sensitivity and specificity of CMOS in caries detection were 57.5% and 82.5%, respectively. Incorrect diagnoses (FP+FN) were equal to 35% for PSP and 30% for CMOS (P=0.89). Conclusion: The results indicated that PSP and CMOS sensors have similar abilities in the detection of secondary caries under amalgam restorations, while none of the two sensors has the adequate ability for a precise and thorough diagnosis of secondary caries.